A Qualitative Analysis of the Commercial Broiler System, and the Links to Consumers' Nutrition and Health, and to Environmental Sustainability: A South African Case Study - Queenan, Kevin; Cuevas, Soledad; Mabhaudhi, Tafadzwanashe; Chimonyo, Michael; Slotow, Rob; Häsler, Barbara (Frontiers in Sustainable Food Systems, 2021)
Food systems face growing challenges to meet targets of Zero Hunger (SDG 2), and South Africa is no exception given its triple burden of malnutrition, foodborne disease outbreaks, and threats of climate change to food production. Broiler meat is South Africa's most affordable meat option, supporting household food and nutrition security. Although considered healthier and less environmentally harmful than ruminant meat, it is not without food safety risks and environmental impacts. This research aimed to present the foremost commercial broiler system narratives in South Africa, around targets of SDG 2, and to discuss key considerations for policymakers. Twenty-nine key informants and stakeholders, purposively selected to cover a wide range of opinions, participated in semi-structured interviews. Transcripts underwent a qualitative framework analysis. Results showed a highly efficient system, dominated by a small number of interlinked large-scale actors, vulnerable to competition from cheaper imports, yet pressurized to maintain high food safety and environmental impact standards, with a price-sensitive consumer base. Existing policies lack integration and enforcement capacity, and are undermined by siloed government departments, and mistrust and power struggles between public and private sectors. We propose removal of silo walls, and trust building through participatory policy development, with collaborative and transformative public-private partnerships that are designed to build capacity to deliver sustainable solutions.